Time-Dependent Displacement of Commensal Skin Microbes by Pathogens at the Site of Colorectal Surgery. (24th October 2020) - Holder-Murray, Jennifer; Yeh, Andrew; Rogers, Matthew B; Firek, Brian; Mahler, Brandon; Medich, David; Celebrezze, James; Morowitz, Michael J
Abstract: Background: Although the healthy human skin microbiome has been the subject of recent studies, it is not known whether alterations among commensal microbes contribute to surgical site infections (SSIs). Our objective in this study was to characterize temporal and spatial variation in the skin microbiota of patients undergoing colorectal surgery and determine if dysbiosis contributes to SSIs. Methods: Sixty one adults scheduled to undergo elective colon or rectal resection were identified by convenience sampling. By analyzing bacterial 16S rRNA gene sequences isolated from clinical samples, we used a culture-independent strategy to monitor perioperative changes in microbial diversity of fecal samples and the skin. Results: A total of 990 samples from 61 patients were analyzed. Alpha diversity on the skin decreased after surgery but later recovered at the postoperative clinic visit. In most patients, we observed a transient postoperative loss of skin commensals ( Corynebacterium and Propionibacterium ) at the surgical site, which were replaced by potential pathogens and intestinal anaerobes (eg, Enterobacteriaceae ). These changes were not observed on skin that was uninvolved in the surgical incision (chest wall). One patient developed a wound infection. Incisional skin swabs from this patient demonstrated a sharp postoperative increase in the abundance of Enterococcus, which was also cultured from wound drainage. Conclusions: We observed reproducible perioperative changes in the skin microbiome following surgery. The low incidence of SSIs in this cohort precluded analysis of associations between dysbiosis and infection. We postulate that real-time monitoring of the skin microbiome could provide actionable findings about the pathogenesis of SSIs. Abstract : Perioperative changes in the skin microbiome at the surgical site generally consist of a transient loss of skin commensals and a compensatory increase in the abundance of potential pathogens and anaerobes from the gut. We postulate that real-time monitoring of the skin microbiome, in parallel with improved knowledge of the gut microbiome and gastrointestinal surgery, could provide actionable findings about the pathogenesis of surgical site infections.